Power Quality Issues in Dispersed Generation and Smart Grids - Vaimann, T.; Niitsoo, J.; Kivipõld, T.; Lehtla, T. (Elektronika ir Elektrotechnika, 2012)
The world today is moving toward smart distribution grids and dispersed generation. Those tendencies are caused by different reasons. These include the decrease of fossil fuel consumption, EU directives of CO2 emissions and climate objectives etc. Innovation and change in technology is a highly welcomed trend but one must not forget that there are drawbacks as well as benefits. One of the most important issues in future grids are the power quality and supply reliability issues. This paper describes how the change to dispersed generation and smart grids should look like and what are the main problems, that need quick and active solutions, so that future grids would be fully functional and reliable. DOI: http://dx.doi.org/10.5755/j01.eee.18.8.2605